Early Childhood Faith Education Trought Story Telling - Munafiah, Nida’ul (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2018)
This study aims to determine the education of early childhood faith through stories in the TKITA1 group At-Taqwa Grabag Magelang. The research methodology used uses a qualitativeapproach. The technique used in this study is the technique of observation, interviews,documentation with data collection tools, namely interview guides, observation, documentationand field notes. The population in this study were all A1 group children, totaling 22 people withone class teacher and one accompanying teacher. The results showed that the education ofearly childhood faith through storytelling applied at the At-Taqwa Grabag TKIT in Magelang wasconducted using picture books, videos, and using teaching aids such as hand puppets, fingerpuppets, puppets, and flannel boards. The storytelling activity was carried out at least once amonth especially on Friday as the development of children's faith education through narrating,coloring and writing the name of the Prophet's heart. Plans for learning activities that areoriented towards faith education through narrating at TKIT At-Taqwa Grabag in the oddsemester of school year 2018/2019 including the story of the prophet Adam, the story ofAbraham and Ismail (using video media), the story of the prophet Muhammad and the story ofProphet Moses